Experimental analysis of materials in proton exchange membrane electrolysis cells. (22nd October 2019) - Ferriday, T.; Middleton, P.H.
Abstract: An accelerated supply and demand of energy has resulted in an increased need for efficient energy storage options, where storing energy in hydrogen gas emerges as one of the most attractive. In this study, a singular proton exchange membrane (PEM) electrolysis cell was designed using adequately low-cost materials, and tested using polarisation curves, cyclic voltammetry and AC impedance. A comparative study of various micro porous layer (MPL) materials was performed in an effort to find suitable options which are able to steadily operate under anodic conditions. The best performance was achieved using carbon cloth, however this material was unstable. Untreated porous titanium and nickel displayed increased stability, though these materials require further development to match the initial performance of carbon cloth as an MPL material. Highlights: A low-cost proton exchange membrane electrolysis cell was designed and built. A comparative study of several micro porous layer (MPL) materials was performed. Carbon cloth was found unstable under anodic conditions. Porous metal MPL materials displayed superior stability. Further development is needed to enhance the performance of the porous metal MPLs.